INCREASED RESISTANCE OF PENAEUS MONODON TO WHISPOVIRUS CAUSES WHITE SPOT SYNDROME THROUGH ANTIVIRUS GENE TRANSFER - Chelvieana A. Christanti; Debora V. Widyanti; Yesica C. Rhenata; Floreta D. Icasari; David L Gultom; Sudarsono Siburian; Wahyu Irawati (Universitas Medan Area, 2021)
The shrimp species Penaeus monodon is the main commodity of Indonesian aquaculture. One of the obstacles when cultivating tiger prawns is the attack of white spot disease (White Spot Syndrome Virus) which makes the quality and quantity of production decrease. One attempteffective for overcoming the white spot virus attack on shrimp, namely through the transfer of antiviral genes. Previous researchers carried out the transfer of antiviral genes to provide immunological effects so that they were resistant to pathogen attack and could prevent the death of tiger prawns. Destinationwriting article that is This study aims to determine the increase in resistance of tiger shrimp to Whispovirus that causes White Spot Syndrome through the transfer of antiviral genes. The type of research conducted is descriptive qualitative with a literature review method that discusses five focus studies, namely Whispovirus as a cause of White Spot Syndrome Virus (WSSV) disease in tiger prawns, tiger shrimp infected with White Spot Syndrome Virus, the use of PmAV antiviral genes in the treatment of Whispovirus , the mechanism of transfection of antiviral genes in the treatment of Whispovirus infection against tiger prawns, and changes in tiger shrimp resistance after insertion of antiviral genes. The conclusion obtained is that the addition of antiviral genes in tiger shrimp DNA can increase its resistance to Whispovirus.